Role of Diethylstilbestrol on Growth of Green Chromide, Etroplus suratensis - V., Jayaprakas; C., Sambhu (Fishery Technology, 2025)
Green chromide was cultured by feeding diets supplemented with five levels (1, 2, 3, 4 and 5 ppm) of diethylstilbestrol for 120 days in a brackish water pond and its growth performance was evaluated. Diethylstilbestrol at 2 ppm level produced significantly (p